Value of Intraoperative Transesophageal Echocardiography during tetralogy of Fallot repair - Borodinova, O. (Ukrainian Journal of Cardiovascular Surgery, 2018)
This study was performed to define a value of intraoperative transesophageal echocardiography (ITEE) during tetralogy of Fallot (ToF) repair. Methods. Intraoperatively 64 patients with ToF were examined by TEE before and after cardiopulmonary bypass (CPB). Results. All preoperative diagnosis were confirmed by ITEE, except two cases when ITEE excluded diagnosis of PA branches’ stenosis and one case when additional muscular ventricular septal defect was detected. Was revealed a strong correlation of PV annulus Z-score diameter by ITEE with intraoperative data (r=0,802; p<0.00001). Significant RVOTO was detected by ITEE in two patients (3,1%) and three patients (4,7%) underwent a reoperation on pulmonary branches due to ITEE data. Conclusions. ITEE imaging is a valuable, safe and accurate tool for anatomical, hemodynamic, and functional assessment during ToF repair.